Variabel-Variabel yang Memengaruhi Kualitas Pembangunan Manusia Kabupaten/Kota di Provinsi Maluku Utara Tahun 2015-2022 - Saputra, Martino Dwi; Budyanra, Budyanra (Seminar Nasional Official Statistics, 2024)
Based on the preamble of the 1945 Constitution, the national goals of Indonesia are to promote the general welfare and to educate the nation's life. This can be seen through the quality of human development. Despite North Maluku Province having an economic growth rate consistently above the national average and a poverty rate consistently below the national average from 2015 to 2022, its human development quality remains below the national level, which is contradictory. This study aims to analyze the variables that influence the quality of human development in the regencies/cities of North Maluku Province from 2015 to 2022. The method used is panel data regression analysis. The results of the study show that internet access, electricity access, and access to proper sanitation positively impact the quality of human development, while the Open Unemployment Rate negatively impacts the quality of human development in the regencies/cities of North Maluku Province from 2015 to 2022. To improve the quality of human development, the government can implement appropriate policies targeting the factors that influence human development quality.